Rapid degradation of N-3-oxo-acylhomoserine lactones by a Bacillus cereus isolate from Malaysian rainforest soil - Chan, Kok Gan; Wong, Cheng Siang; Yin, Wai Fong; Sam, Choon Kook; Koh, Chong Lek (Springer, 2010)
A bacterial strain, KM1S, was isolated from a Malaysian rainforest soil sample by using a defined enrichment medium that specifically facilitates selection of quorum quenching bacteria. KM1S was clustered closely to Bacillus cereus by 16S ribosomal DNA sequence analysis. It degraded N-3-oxo-hexanoyl homoserine lactone and N-3-oxo-octanoyl homoserine lactone in vitro rapidly at 4.98 and 6.56 mu g AHL h(-1) per 10(9) CFU/ml, respectively, as determined by the Rapid Resolution Liquid Chromatography. The aiiA homologue, encoding an autoinducer inactivation enzyme catalyzing the degradation of N-acylhomoserine lactones, of KM1S was amplified and cloned. Sequence analysis indicated the presence of the motif (106)HXDH-59 amino acids-H(169)-21 amino acids-D(191) for N-acylhomoserine lactone lactonases.